IDENTIFIKASI DAN ANALISIS PRAKTIK LANDASAN KURIKULUM DALAM PEMBELAJARAN SEKOLAH DASAR DI SDN 184 DARE AJUE KABUPATEN SOPPENG - Anisa Waliyyu Ruman; Suardi (STKIP Subang, 2026)
This study aims to identify and analyze the implementation of philosophical, psychological, sociological, and cultural foundations in elementary school learning at SDN 184 Dare Ajue, Soppeng Regency. A qualitative approach was employed using interviews, classroom observations, document analysis, and student group discussions. The findings indicate that learning practices reflect progressive and constructivist principles through active learning, group work, and the integration of Pancasila values. Instructional strategies have been adapted to students’ developmental characteristics in a contextual manner. However, the integration of sociological and cultural aspects, particularly the use of local culture, has not been systematically planned in instructional documents. This study recommends strengthening instructional planning to explicitly integrate the four curriculum foundations in order to create more meaningful, humanistic, and contextual learning experiences.